2012
DOI: 10.1515/ijdhd-2012-0037
|View full text |Cite
|
Sign up to set email alerts
|

Promoting leadership and intrapersonal competence in university students: what can we learn from Hong Kong?

Abstract: To promote leadership and intrapersonal competence in university students, a general education course based on the positive youth development approach was developed at The Hong Kong Polytechnic University in Hong Kong. The course was piloted in four classes of students in the 2010/11 academic year. After completion of the course, subjective outcome evaluation data based on a validated instrument were collected from 189 students. Results showed that the students generally had positive perceptions of the program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 33 publications
7
25
1
Order By: Relevance
“…The present fi ndings are consistent with the evaluation fi ndings based on other evaluation strategies (28,29) . Utilizing subjective outcome evaluation fi ndings collected from 189 students taking this course, results showed that students generally had positive perceptions of the program and implementers, with over 90 % of the participants indicating that they were satisfi ed with the program and that the program was perceived as helpful to them in the domains of holistic development and leadership (30) .…”
Section: Discussionsupporting
confidence: 91%
“…The present fi ndings are consistent with the evaluation fi ndings based on other evaluation strategies (28,29) . Utilizing subjective outcome evaluation fi ndings collected from 189 students taking this course, results showed that students generally had positive perceptions of the program and implementers, with over 90 % of the participants indicating that they were satisfi ed with the program and that the program was perceived as helpful to them in the domains of holistic development and leadership (30) .…”
Section: Discussionsupporting
confidence: 91%
“…The Chinese Positive Youth Development Scale is a validated scale based on different samples. Second, subjective outcome evaluation for the lectures and the course was carried out (20) . Third, process evaluation of some of the lectures was carried out (21) .…”
Section: Criticism 4: It Is Diffi Cult To Evaluate Courses On Personamentioning
confidence: 99%
“…To test out the curriculum, " Tomorrow ' s Leaders " was offered in the second term of the 2010/2011 academic year on a pilot basis. Although the evaluation findings based on the SOES were very encouraging, the dimensionality of the scale was not reported in the article [12] . As the subject was piloted again in the first term of the 2011/2012 academic year, it is a good opportunity to examine the psychometric properties of the scale.…”
Section: Introductionmentioning
confidence: 99%